Potential Induced Degradation Effect On N-Type Solar Cells With Boron Emitter - Mojrová, Barbora (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
This study is focusing on Potential Induced Degradation (PID) effect on n-type solar cells with boron emitter. We designed and fabricated single cell modules using n-PERT cells with textured and flat front side, and with various passivation structures on the front side to prevent PID at the cell level. The modules were characterized before and after PID testing by electroluminescence (EL), IV measurements, reflection and Internal Quantum Efficiency (IQE). Measurements were done on both sides of module to obtain whether the degradation was going on the front side, rear side or both. Comparison of IQE of front vs rear side shows, that intensity of degradation is fully influenced by properties of the front side of antireflection and passivation (ARC) layer.
Keywords: PID; n-type; solar cell; passivation layer; boron emitter